Organizational Mechanism of Regional Socio-economic Welfare Monitoring; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Nekhoda E. V. Evgeniya Vladimirovna (2016, 2016)
Title screen